دور الوقف في تخفيف العبء عن الموازنة العامة دراسة مطبقة على الموازنة المصرية - عبد الكريم أحمد, أحمد عبد الصبور (Recherches économiques et managériales, 2013)
يهدف هذا البحث إلى الكشف عن دور الوقف في تخفيف العبء عن الموازنة العامة للدولة، وذلك من خلال معرفة الدور التنموي للوقف ومساهمته في النفقات العامة في مصر. ويحاول هذا البحث إجلاء الدور الحضاري والتنموي للوقف في التاريخ الإسلامي، وكذلك الحاجة الملحة لإحياء دور الوقف في المجتمعات الإسلامية، وإمكانية الاستفادة منه لتخفيف الأعباء الملقاة على عاتق الدولة، خاصة وأن جميع الدول تقريباً تعاني من عجز مستمر في ميزانياتها العامة. الأمر الذي ترتب عليها تقصير الدولة في القيام بدورها الاقتصادي والاجتماعي تجاه المجتمع، وكذلك زيادة حجم المديونيات الداخلية والخارجية، وارتفاع نسبة التضخم والبطالة. وقد أثبت البحث ان تدخل الدولة في الوقف وفرض وصايتها عليه كان سبباً رئيسياً في إضعاف الوقف وتحجيم دوره في التنمية. كما ترتب على هذا التدخل اندثار ثقافة الوقف في معظم المجتمعات الإسلامية تقريباً، كما يثبت البحث أن حسن استغلال الوقف يمكن أن يساهم في تخفيف العبء عن الموازنة العامة للدولة، وذلك من خلال توفيره للخدمات والسلع العمومية في المجتمع، وبالتالي تخفيف العبء عن الدولة، ومن ثم تحقيق التنمية الشاملة. وبناء على ما توصل إليه البحث من نتائج فقد اوصى بمجموعة من التوصيات التي من الممكن ان تساهم في إحياء الدور الحضاري والتنموي للوقف. Abstract This research aims at revealing the role of endowment on reducing the burden on the public budget of the country through knowing the developmental role of endowment and its contribution in public expenses in Egypt. This research try to reveal the civilized and developmental role of endowment in Islamic history, the urgent need to revival the role of endowment in Islamic societies, the ability of benefit from endowment for reducing the burden on the country nowadays especially that nearly all the countries face a continuous deficit in their public budgets and that lead to a shortage of the economical and social role of the country toward the society, also the increase amount of the internal and external debts and the increase percent of inflation and unemployment. The research has proved that the intervention of the country in endowment was a main reason of weakening endowment and limiting its role in the economical and social development in society and vanishing the culture of endowment in most Islamic countries, the results revealed also that endowment – if it is used well, can contribute in decreasing the burden on the public budget of society through its economical and social role as endowment provides services and public goods in society and that decrease the burden on the country and achieving the comprehensive development. The research provided recommendations that probably contribute in revival the civilized and developmental role of endowment in contribution in the public expense and reduce the burden on the public budget in the Islamic societies.